1994
DOI: 10.1159/000246819
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of H<sub>1</sub> Blockers by Noninvasive Measurement Techniques

Abstract: Background: Evaluation techniques for determining the strength of action and the onset of activity of H1 receptor blockers have not yet been sufficiently standardized. Objective: The clinical efficacy of the H1 receptor blocker loratadine was to be measured upon a wheal response subsequent to an intracutaneous injection of 0.1 ml histamine (0.1%). Methods: In a pilot study, 10 patients were treated with the H1 receptor blocker loratadine for a period of 7 days. Various noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
2
8
0
1
Order By: Relevance
“…Along with other trials on experimental inflammatory dermatoses [18,22], this latter study [23] indicates that sonography images dermal edema as an echo-poor zone within the dermis. Gniadecka and Quistorff [24] produced evidence that echogenicity is a valid parameter for changes in dermal water content.…”
Section: Experimental Approachessupporting
confidence: 63%
See 2 more Smart Citations
“…Along with other trials on experimental inflammatory dermatoses [18,22], this latter study [23] indicates that sonography images dermal edema as an echo-poor zone within the dermis. Gniadecka and Quistorff [24] produced evidence that echogenicity is a valid parameter for changes in dermal water content.…”
Section: Experimental Approachessupporting
confidence: 63%
“…Furthermore, 20-MHz B-scan ultrasound permits the quantitative evaluation of the efficacy of H1 receptor blockers by measuring the wheal response to an intracutaneous injection of 0.1 ml histamine (0.1%) [23]. Hoffmann et al [23] reported that the urticarial reaction, which could be detected sonographically prior to its clinical appearance, was significantly reduced in patients who had been treated with 10 mg loratadine over a period of 7 days.…”
Section: Experimental Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a videocamera, the outlined areas are then scanned into an analysis programme integrated in a PC with video interface. The area, circumference and diameter were determined automatically by means of an analysis programme (Micro Scale, Digithurst, UK) [19].…”
Section: Planimetrymentioning
confidence: 99%
“…In Germany, the combination of nonivamide and nicoboxil (Finalgon ® ) has been used for the treatment of rheumatic muscular, arthritic and neuralgic pain and of traumatic injuries for decades [15]. The hyperemic reaction can be determined quantitatively both directly by laser Doppler perfusion imaging [16][17][18] and indirectly by planimetry [19].…”
Section: Introductionmentioning
confidence: 99%